Indigenous Conceptions of Conversion among African Christians in South Africa - Masondo, Sibusiso (Journal for the study of religion, 2015)
The paper explores the meaning of conversion for African Christians in South Africa by looking at some of the indigenous terms that have populated the Christian vocabulary. The paper focuses on terms likeukuguquka, ukukholwa, ibandla, ikholwa, igqobhoka, inkonzo,andinkolo. These terms are found among people who speak Nguni languages. It shows how they were used in pre-Christian context and traces their evolution in Christian contexts. Research conducted in the Reformed Presbyterian Church, St John’s Apostolic Faith Mission, and Methodist Churches in Cape Town between 1997 and 2001 has indicated that conversion was not a simple religious process but involved diverse political, economic and social aspects. Conversion involved a transformation of an African Christian identity from the margins to the centre. It also involved extensive negotiation of what it means to be Christian through the translation of Christian content into an African idiom. The paper goes through various terms and how their original meanings were discarded for new ones.